1991
DOI: 10.1093/nar/19.11.3055
|View full text |Cite
|
Sign up to set email alerts
|

Targeted gene walking polymerase chain reaction

Abstract: We describe a modification of a polymerase chain reaction method called 'targeted gene walking' that can be used for the amplification of unknown DNA sequences adjacent to a short stretch of known sequence by using the combination of a single, targeted sequence specific PCR primer with a second, nonspecific 'walking' primer. This technique can replace conventional cloning and screening methods with a single step PCR protocol to greatly expedite the isolation of sequences either upstream or downstream from a kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
88
1

Year Published

1992
1992
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(93 citation statements)
references
References 13 publications
3
88
1
Order By: Relevance
“…By attaching to ubiquitous genomic sequences, this nonspecific walking primer could support the first primer in generating fragments within a 5 kb size range, a strategy that was first applied in targeted gene walking PCR. 86 Although we did not demonstrate that the generated PCR products are within genes or that the PCR products generated, e.g., with the TATA primer indeed encompass TATA boxes, other groups have shown that PCR with degenerate primers that encode conserved amino acid sequences can be used to screen animal genomes reliably for likely gene family members. 87 In this way, we think that we increased the possibility of amplifying these regions.…”
Section: Resultscontrasting
confidence: 55%
“…By attaching to ubiquitous genomic sequences, this nonspecific walking primer could support the first primer in generating fragments within a 5 kb size range, a strategy that was first applied in targeted gene walking PCR. 86 Although we did not demonstrate that the generated PCR products are within genes or that the PCR products generated, e.g., with the TATA primer indeed encompass TATA boxes, other groups have shown that PCR with degenerate primers that encode conserved amino acid sequences can be used to screen animal genomes reliably for likely gene family members. 87 In this way, we think that we increased the possibility of amplifying these regions.…”
Section: Resultscontrasting
confidence: 55%
“…This lysate was used to transduce strain JE3777 to tetracycline resistance. Arbitrary primer PCR was used to identify a DNA sequence flanking the linked insertion (37,38). Chromosomal DNA of strain JE3845 was prepared using the MasterPure TM genomic DNA isolation kit (Epicentre, Madison, WI).…”
Section: Mapping the Glta Gtg Mutationmentioning
confidence: 99%
“…These primers amplify a fragment approximately 1600 bp in size. By using an additional set of four primer pairs (Table 1), 'targeted gene-walking PCR ' (Parker et al, 1991;Chang et al, 2001) was used to amplify further viral RT-PCR products. The general conditions for RT-PCR have been described previously (Liu & Kong, 2004).…”
mentioning
confidence: 99%